2011
DOI: 10.1021/nn200162z
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxides Dispersing and Hosting Graphene Sheets for Unique Nanocomposite Materials

Abstract: Graphene oxides (GOs), beyond their widely reported use as precursors for single-layer graphene sheets, are in fact excellent materials themselves (polymers in two-dimension, polyelectrolyte-like, aqueous solubility and biocompatibility, etc.). In this reported work we used aqueous GOs to effectively disperse few-layer graphene sheets (GNs) in suspension for facile wet-processing into nanocomposites of GNs embedded in GOs (as the polymeric matrix). The resulting lightweight and plastic-like nanocomposite mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 46 publications
4
68
0
Order By: Relevance
“…[[qv: 21b]],67 However, the dispersion of fluorographene in solvents is crucially important for the solution‐processed fabrication of devices or applications as precursors for electrodes and composites. [[qv: 26b]],[[qv: 26e]],68 Previous studies reported that hydrophobic fluorographene could not be dispersed in ethanol because it has no free p z orbitals to form pseudohydrogen bonds with the hydroxy group of ethanol. [[qv: 13a]] The pseudohydrogen bond has been demonstrated to facilitate the dispersion of graphene with the π bond (abundant free p z orbitals) in ethanol.…”
Section: Propertiesmentioning
confidence: 99%
“…[[qv: 21b]],67 However, the dispersion of fluorographene in solvents is crucially important for the solution‐processed fabrication of devices or applications as precursors for electrodes and composites. [[qv: 26b]],[[qv: 26e]],68 Previous studies reported that hydrophobic fluorographene could not be dispersed in ethanol because it has no free p z orbitals to form pseudohydrogen bonds with the hydroxy group of ethanol. [[qv: 13a]] The pseudohydrogen bond has been demonstrated to facilitate the dispersion of graphene with the π bond (abundant free p z orbitals) in ethanol.…”
Section: Propertiesmentioning
confidence: 99%
“…Among these methods, chemical reduction of GO is the most promising approach leading to large-scale production of graphene. Although its effectiveness on the conversion of GO to restore the intrinsic graphene structure is still in debate, there is an emerging realization on the excellent properties of GO for material applications [11]. GO is easily obtained from natural graphite flakes by the strong oxidation and subsequent exfoliation based on the Hummers method [12].…”
Section: Introductionmentioning
confidence: 99%
“…Second, it is well known that GO film has porous structures, which can provide an efficient path for water supply and vapor flow (22)(23)(24)(25)(26)(27)(28)(29)(30). Third, the crossplane thermal conductivity of GO film is very low (∼0.2 W/mK) (31,32), beneficial for suppressing the parasitic thermal dissipation. Fourth, GO film is highly foldable and can be naturally attached to cellulose (33,34), so that the water pumped by capillary force within the cellulose can be efficiently transferred to GO film.…”
mentioning
confidence: 99%